Efficacy of modified thoraco-laparoscopic Ivor-Lewis versus traditional thoraco-laparoscopic Ivor-Lewis for esophageal cancer: Propensity score-matched analysis - Hong, Ziqiang; Gou, Wenxi; Lu, Yingjie; Wu, Xusheng; Sheng, Yannan; Cui, Baiqiang; Bai, Xiangdou; Jin, Dacheng; Gou, Yunjiu (Frontiers in Oncology, 2023)
Objective To compare the clinical results of the modified Ivor-Lewis procedure, which preserves the azygous vein, thoracic duct and surrounding tissues, with the traditional Ivor-Lewis procedure, which removes these tissues, for treating esophageal squamous cell carcinoma, and evaluating whether the azygous vein, thoracic duct and surrounding tissues are required to be removed for the surgery of esophageal cancer. Methods To retrospectively analyze the clinical data of patients suffering from esophageal cancer treated by thoracic-laparoscopic Ivor-Lewis procedure admitted to the Department of Thoracic Surgery of Gansu Provincial People’s Hospital from September 2017 to September 2019. According to the surgical method, they were divided into the modified thoracolaparoscopic Ivor-Lewis (modified group) and the traditional thoracolaparoscopic Ivor-Lewis (traditional group). Propensity score matching analysis (PSM) was applied to reduce the selection bias of confounding factors. Results A total of 245 patients who suffered from esophageal cancer and underwent thoracic-laparoscopic Ivor-Lewis were enrolled in the study. There were 124 cases in the modified group and 121 cases in the traditional group. The discrepancies in the age and T-stage among patients in the traditional and modified groups were statistically significant. After PSM, the above-mentioned factors became statistically insignificant. There were 86 patients in each group after PSM. Compared with the traditional group, the modified group has shorter operative time (p=0.007), less intraoperative bleeding (p=0.003) and less postoperative 3 days chest drainage(p=0.001), with a statistically significant difference. No significant difference in local recurrence (p=0.721) and distant metastasis (p=0.742) after surgery were found in the two groups, and the difference was not statistically significant. There was also no statistically significant difference in the 3-year postoperative survival rate (44.2% vs. 41.9%, p=0.605) between the modified and traditional groups. Conclusion The modified Ivor-Lewis procedure, which preserves the azygous vein, thoracic duct, and surrounding tissue, reduces surgical trauma in esophageal cancer, has not increased postoperative recurrent metastases, while achieved the same long-term outcomes as expanded surgery.